2019
DOI: 10.3390/pharmaceutics11030130
|View full text |Cite
|
Sign up to set email alerts
|

The Self-Assembly Phenomenon of Poloxamers and Its Effect on the Dissolution of a Poorly Soluble Drug from Solid Dispersions Obtained by Solvent Methods

Abstract: The self-assembly phenomenon of amphiphiles has attracted particular attention in recent years due to its wide range of applications. The formation of nanoassemblies able to solubilize sparingly water-soluble drugs was found to be a strategy to solve the problem of poor solubility of active pharmaceutical ingredients. Binary and ternary solid dispersions containing Biopharmaceutics Classification System (BCS) class II drug bicalutamide and either Poloxamer®188 or Poloxamer®407 as the surface active agents were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 70 publications
2
21
0
Order By: Relevance
“…It leads to the conclusion that thermal analysis and its parameters, e.g., glass transition point (T g ), do not exhibit quantitative relationships with BCL dissolution patterns. This conclusion is consistent with the findings of Szafraniec et al (10) of the mechanism responsible for promotion of dissolution rate and extent of BCL in BCLpoloxamer (PLX) solid dispersions, which is not based completely on amorphization but on the solubilizing effect of Fig. 2.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It leads to the conclusion that thermal analysis and its parameters, e.g., glass transition point (T g ), do not exhibit quantitative relationships with BCL dissolution patterns. This conclusion is consistent with the findings of Szafraniec et al (10) of the mechanism responsible for promotion of dissolution rate and extent of BCL in BCLpoloxamer (PLX) solid dispersions, which is not based completely on amorphization but on the solubilizing effect of Fig. 2.…”
Section: Discussionsupporting
confidence: 93%
“…Bicalutamide (BCL), a non-steroidal antiandrogen drug, exhibits aqueous solubility as low as 3.7 μg/mL and is well absorbed following oral administration (3,4), which classifies BCL to class II of the Biopharmaceutics Classification System (BCS) (5). Researchers reported in the literature improved dissolution of the powder systems with BCL by complexation with β-cyclodextrin (6,7), preparation of solid dispersions using solvent evaporation method (8)(9)(10)(11), milling (12,13), hot melt extrusion (14,15), and formation of co-amorphous systems (16). Desired dissolution improvement was achieved by trial and error approach, applying various qualitative, quantitative composition, and preparation methods under different conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It is then possible to speculate that the adsorbed P388 was in a brush-like configuration promoted by the high hydrophobicity of silicone [23]. The brush-like configuration is the preferred one for our purposes since the hydrophilic PEO brushes could hinder bacterial adhesion by hydration and steric hindrance effects [24].…”
Section: Resultsmentioning
confidence: 99%
“…The micellar systems MS-EZ (1:0.25) and MS-EZ (1:1) showed significant increases of 2.46- and 2.59-fold ( p < 0.05) at 10 min compared to EZ-RM ( Figure 4 A). Different studies indicated that surfactants such as Kolliphor RH40 or Tween 80 are especially suitable for the formation of micelles and increase the solubility of poorly solubility drugs [ 27 , 28 ]. The commercial tablet Ezetrol showed a release percentage of 75.52 ± 2.13% at 10 min.…”
Section: Resultsmentioning
confidence: 99%